DEVELOPMENT OF FLEXIBILITY IN 8–10-YEAR-OLD GIRLS ENGAGED IN RHYTHMIC GYMNASTICS - Khaytmetov, I.S. (SCIENCE and SOCIETY, 2026)
The article discusses the development of a comprehensive set of exercises aimed at developing flexibility in 8-10-year-old girls, taking into account the anatomical and physiological characteristics and the necessary loads for optimizing and developing the flexibility of 8-10-year-old gymnasts.
Keywords: pedagogical observation; pedagogical experiment; mathematical analysis; flexibility; endurance; strength; physical training; technical training; special physical training; artistic gymnastics exercises; practical skills; theoretical knowledge